L'activité communicationnelle enseignante lors des discussions à visée philosophique - Valérie Saint-Dizier de Almeida; Antonietta Specogna; Christophe Luxembourger (Nantes Université, 2016)
The paper deals with animation in Collaborative philosophical Inquiry. Like psychologists ergonomists, we develop that to design training on communicational activity (animation in CPI in this case), it's necessary to understand this activity through the study of its accomplishment. To improve the understanding of animation in CPI and to identify different styles of animation, we propose to study nine CPI transcribed involving three elementary school teachers. We present models and methodologies used. Your framework borrowed from social psychology, ergonomic psychology and language sciences. We propose to study the role of teachers/animators in the communication distribution, in the functional structuring of the activity and so, we identify the functions that their behaviors enable them to accomplish. From the results, animation styles are identified.